ANALISIS TEORI KRIMINOLOGI STRAIN DALAM KASUS BALAP LIAR - Manullang, Clara Jennifer (UNES Law Review, 2023)
This analysis aims to examine the influence of strain criminology theory in cases of wild racing. This theory explains that the pressure or tension experienced by individuals due to an imbalance between desired social goals and available resources can encourage criminal behavior. In the case of street racing, strain theory can explain how individuals who face certain economic, social, or emotional pressures are drawn to engage in street racing. Through secondary data analysis, including case studies and relevant literature, the results of this study will provide further understanding of the role of strain criminology theory in the phenomenon of wild racing and its implications for prevention efforts.